Ecological values of the modern youth culture - Z. M. Isaeva; R. M. Abakarova (Юг России: экология, развитие, 2015)
High cultural level of the population promotes formation of cultural level of growing generations where a special place should be given the formation of ecological culture. Ecological crisis places under threat the opportunity of further existence of the person and the nature; it is caused by not only social and economic, technical and technological or political reasons but also by reasons of spiritual order. The importance of such notions as spirituality, competence, erudition has fallen yet. Formation of ecological culture as the ultimate goal of ecological education includes some stages: formation of knowledge; formation of values; bringing of the knowledge and value components to the activity plan. In the process of ecological education the ecologically active person must be brought up, who, with interest, on the basis of deep ecological knowledge exploits the environment with the view of creation of optimum ecological conditions of life of the person.